Critérios ambientais em um modelo de suporte à decisão no planejamento de estradas florestais - Américo, Carla (Universidade Federal de São Carlos, 2023)
When not well structured and allocated, forest roads become potential sources of environmental impacts, especially those related to water dynamics and sediment production. In this context, the general objective was to present an approach for planning forest roads focused on hydrological conservation, topography, and soil stability, with the use of multicriteria evaluation (MCE). For this, the thesis was structured in chapters, in which the first one brings a review about forest roads and methodologies currently used for their planning and optimization. In the second chapter, considering that the soil map is essential for environmental analysis, and that it is commonly represented in classes, a continuous soil map was elaborated by means of fuzzy logic and geostatistics, evaluating the output map of the MCE model from a sensitivity analysis.In the third chapter, from MCE we integrated the criteria slope, erodibility, distance to the hydrographic network and topographic wetness index, to obtain the environmental fragility in two forest production farms. In the fourth chapter, the importance of the previously selected criteria that supported priority areas for forest road allocation was evaluated using the Weighted Linear Combination (WLC) method. In the fifth chapter, the performance of the Ordered Weighted Average (OWA) method was evaluated in relation to the WLC method, in the prioritization of areas for forest road allocation, considering the previously selected criteria. As a general conclusion, supported by the results of the chapters, it was obtained that it is possible to use the WLC method in the planning of forest roads, which obtained good performance proven by the sensitivity analysis. Thus, the proposed decision model leads to the optimization of resources and actions, which will ensure that forest enterprises will have access to the stands throughout the year, as well as the conservation of water and soil in the landscape.
Environmental criteria in a decision support model for the planning of forest roads
Keywords: Krigagem; Lógica Difusa; Fragilidade Ambiental; Avaliação Multicriterial; Análise de Sensibilidade; Planejamento Florestal; Kriging; Fuzzy Logic; Environmental Fragility; Multicriteria Analysis; Sensitivity Analysis; Forest Planning; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNICAS E OPERACOES FLORESTAIS